Hormone induced recipients for embryo transfer in mice - Yeonmi Lee; Eunju Kang (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Embryo transfer (ET) in the animal is an important procedure to generate genetically engineered animals and conserve genetic resources. For ET experiments in mice, pseudopregnant recipients are usually prepared with proestrus stage of females and vasectomized males. However, this conventional method is inefficient because the size of female colonies should be large to select only the proestrus stage in the estrous cycle and the surgical procedures are required to generate vasectomized males. In this study, we established a simple and efficient protocol to prepare ET recipients using the estrous synchronization with hormone injection and the mating with wild male mice. The delivery rate of ET recipients tended to be increased with estrous synchronization using hormone injection (100%) compared to the conventional method (71%). Further, natural pregnancy of the recipients, induced by mating with a wild male, significantly enhanced the birth rate of ET offspring than the conventional method (33% vs. 13%). Based on the results, we concluded that our new protocol using hormone injection to ET recipients and mating with wild males could be more efficient and simpler compared to the conventional method.